FINANCIAL FEASIBILITY STUDY IN THE PUBLIC STREET LIGHTING PROJECT USING PUBLIC-PRIVATE PARTNERSHIP (PPP) SCHEME - Aditia Nugroho, Yoga
The Government of Indonesia estimates that the country will need USD 359.2 billion investment for infrastructure development. However, it is estimated that only 73.5% of the investment value Public Street Lighting (PJU) is one of the most important elements of urban infrastructure. PJU is the main service that must be provided by the government to provide adequate lighting on the streets which is useful for increasing security and safety in the city, as well as increasing visibility or visibility at night. The research method authors doing by Investment valuation, Discounted Cash flow, NPV, IRR, Payback Period, and Availability Payment.